Surgery of the pancreatic cystic echinococcosis: systematic review - Dziri, Chadli; Dougaz, Wejih; Bouasker, Ibtissem (Translational Gastroenterology and Hepatology, 2017)
The prevalence of pancreatic cystic echinococcosis (PCE) in the world is low ranging between 0.2% and 0.6%. The diagnosis of PCE is easy when it is associated to other location such as liver, it became difficult when PCE was isolated simulating other diagnosis such as pseudocyst, a choledochal cyst, serous or mucinous cystadenoma and cystadenocarcinoma. This systematic review aimed to provide evidence-based answer to the following questions: (I) what are the efficient tools to affirm the diagnosis of isolated PCE and (II) what are the best therapeutic strategy for the PCE? An electronic search was performed by two authors (W Dougaz, I Bouasker). Medline, Scopus, Embase, Web of Science, Google Scholar and Cochrane collaboration were consulted. The keywords used were “cyst”, “echinococcosis”, “hydatid cyst” and “pancreas”. All abstracts were analyzed followed by extraction of the full text by the same two authors (W Dougaz, I Bouasker), all divergences were resolved by discussion with C Dziri. Recommendations were based on Oxford’s classification: (I) what are the efficient tools to affirm the diagnosis of PCE? —ultrasound remains the cornerstone of diagnosis. Magnetic resonance imaging (MRI) reproduces the ultrasound defined features of CE better than computed tomography (CT). MRI with heavily T2-weighted series is preferable to CT. Pancreatic duct MRI should be promising to identify a fistula between PCE and pancreatic duct (level of evidence 3—recommendation B); (II) what are the best therapeutic strategy for the PCE? —surgery is the main treatment of PCE. Open approach is validated. The decision depends of the location of PCE: head versus body and/or tail of the pancreas (level of evidence 5—recommendation D): for the head of the pancreas, the tendency is toward conservative surgery. For body and/or tail of the pancreas, the tendency is toward radical surgery. Medical treatment (albendazole) should be prescribed 1 week before surgery and 2 months during postoperative period (level II evidence and grade C recommendation).